Environmental factors and their effect on the occurrence of autism - Tsopanidou, Varvara; Drigas, Athanasios (Technium BioChemMed, 2022)
The etiology of autism is the subject of intense research. Genetic factors are clearly important. Gene mutations, gene deletions, copy number variations (CNVs) and other genetic abnormalities are strongly linked to autism. But no etiology represents more than a relatively small percentage of cases. Environmental factors in recent years are increasingly coming to the forefront of research and study and the interest of researchers is increasingly directed in this direction. This article examines the environmental factors associated with the prenatal period and their relationship to autism.